Dampak Dampak Liberalisasi Perdagangan Terhadap Inflasi di Indonesia - Rangkuti, Suifatiha; Rahmi, Meautia; Nuriyo, Amalia Ndaru; Wahyuni, Ribut Nurul Tri (Politeknik Statistika STIS, 2024)
Globalisation encourages the trade of goods and services between countries without any trade barriers, or known as trade liberalisation. Trade liberalisation can impact the macroeconomic indicators of countries that engage in international trade, one of which is inflation. The purpose of this study is to analyse the effect of trade liberalisation on inflation in Indonesia. The variables used are trade openness and inflation. This study uses autoregressive distributed lag (ARDL) method with the research period 2000 - 2023. In addition, government spending and money supply are also used as control variables. The results show that trade openness can increase the inflation on one untill two years later. Trade openness is also show the same effect in the long run and short run. Meanwhile, government expenditure and money supply also increase inflation in the long run and short run.